Public attitudes to the sentencing of drug offences. (July 2014) - Kirby, Amy; Jacobson, Jessica
This article presents the findings of focus group research into public attitudes to the sentencing of drug offences. The study was commissioned by the Sentencing Council for England and Wales to inform the development of their new guideline on drug offences. There were two main findings: first, participants' responses were generally no more punitive than current sentencing practice for less serious offences; second, participants' overriding concerns were about the harms associated with drug offences rather than the culpability of drug offenders. Thus the findings of the study indicate that lighter sentences for drug 'mules' (as were subsequently introduced by the Sentencing Council's new guideline) would be tolerated by the public. However, if the Council wishes to engage more fully with public opinion it will need to take a closer look at public concerns with harm.